Effective Factors towards First Language Acquisition in Hearing Impaired, Cochlear Implanted Children - Seneviratne, L.C. (My University, 2012)
The main focus of this study is to determine the efficacy of first language acquisition among hearing impaired (HI) children with cochlear implants (CI) and the basic contributory factors which have been premised as mandatory. With the advancement of new technology in the field of audiology, Cochlear Implants have become very popular in the world, although it is yet to be popular in Sri Lanka. Nevertheless, there are about 250-300 candidates who have undergone this CI surgery from 2005 onwards in Sri Lanka. This is a device which is very helpful to hearing impaired individuals with severe to profound hearing loss while conventional hearing aids, invented by Alessandro Volta in 1800, were supportive only up to some extent.